Pengembangan Lks Berbasis Etnomatematika (Budaya Lubuklinggau) Untuk Menumbuhkan Motivasi Belajar Matematika Siswa - Maria Luthfiana; Drajat Friansah; Bunga Marcicilia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to develop student worksheet based on ethnomatematics on the system of three-variable linear equation system for class X MAN 1 (Model) Lubuklinggau and find out the quality of worksheets developed in terms of validity, practicality, and effectiveness. This research is a development study with a 4-D development model (four D model). This model consists of 4 stages of development, namely Define, Design, Develop, and Disseminate. The results of the study, in the validity aspect, the worksheets developed received a category (Good) in the component of language worthiness with an average score of 3.00. In the content eligibility component, it gets a category (Very Good) with an average score of 3.24, while the component in the eligibility component gets a (Good) predicate with an average score of 3.04. The quality of teaching materials is seen from the aspect of practicality included in the criteria (Good) with an average score of 3.13 determined based on the results of students' responses to the worksheet. The effectiveness of worksheets can be seen from the aspects of student motivation at the time before the development of worksheets showing an average score of 3.01 while after showing an average score of 3.74 included in the criteria (Very Good). Conclusion, LKS which was developed based on ethnomatematics has valid, practical and effective criteria used to increase the learning motivation of students in class X MAN 1 (Model) Lubuklinggau. Keywords: Ethnomatematics, LKS, Lubuklinggau Culture, Learning Motivation